Association between gastroesophageal reflux disease and stroke: a bidirectional Mendelian randomization study - Meng, Decheng; Zhang, Xin; Yu, Wenfei; Yin, Guoliang; Chen, Suwen; Liu, Hongshuai; Wang, Linya; Zhang, Fengxia (Frontiers in Neurology, 2024)
Objective: Some previous studies have suggested a potential link between stroke and gastroesophageal reflux disease (GERD). We used a two-sample bidirectional Mendelian randomization (MR) method to explore the causal relationship between stroke and GERD.Design: Summary-level data derived from the published genome-wide association studies (GWAS) were employed for analyses. The single-nucleotide polymorphisms (SNPs) as instrumental variables (IVs) for stroke (n=446,696) and its common subtypes ischemic stroke(IS) (n=440,328), large vessel stroke (LVS) (n=410,484), small vessel stroke (SVS) (n=198,048), cardioembolic stroke (CES) (n=413,304) were obtained from MEGASTROKE consortium. The data on intracerebral hemorrhage (ICH) (n=721,135) comes from UK Biobank. Instrumental variables (IVs) for lacunar stroke (LS) (n=474,348) and GERD (n=602,604) were screened from publicly available genetic summary data. The inverse variance weighted (IVW) method was used as the main MR method.Pleiotropy was detected by the MR-Egger intercept test, MR pleiotropy residual sum and outlier, and leave-one-out analysis. Cochran Q statistics were used as supplements to detect pleiotropy.We found that GERD can causally increase the risk of stroke [IVW odds ratio (OR):